Reducing Mechanical Resonance Time of A Flywheel Energy Storage System by Using A Current Control Algorithm for Satellites - Celikel, Resat; Ozdemir, Mehmet; Aydogmus, Omur (Gazi Univ, 2017)
The orbital period of a satellite is completed with two regions as defined bright and dark. The energy must be stored in the bright region of the orbital path. The flywheel energy stored systems are used to provide energy in the dark region. However, the flywheel mechanical systems have mechanical resonance problems which decrease the system performance. The brushless dc motor operates as a motor with undesirable high-current when exposed the mechanical resonance. In this paper, a current reference method is proposed to decrease the current spike and reduce the time period of the mechanical resonance. The performance of the proposed method has been demonstrated by using simulation results and experimental results.
Keywords: Brushless motors; Mechanical resonance; Current reference method; Energy storage; Flywheel